Galanin family peptides: Molecular structure, expression and roles in the neuroendocrine axis and in the spinal cord - Zhu, Sipin; Hu, Xiaoyong; Bennett, Samuel; Charlesworth, Oscar; Qin, Shengnan; Mai, Yuliang; Dou, Haicheng; Xu, Jiake (Frontiers in Endocrinology, 2022)
Galanin is a neurotransmitter and plays versatile physiological roles for the neuroendocrine axis, such as regulating food intake, insulin level and somatostatin release. It is expressed in the central nervous system, including hypothalamus, pituitary, and the spinal cord, and colocalises with other neuronal peptides within neurons. Structural analyses reveal that the human galanin precursor is 104 amino acid (aa) residues in length, consisting of a mature galanin peptide (aa 33 62), and galanin message-associated peptide (GMAP; aa 63-104) at the C-terminus. GMAP appears to exhibit distinctive biological effects on anti-fungal activity and the spinal flexor reflex. Galanin-like peptide (GALP) has a similar structure to galanin and acts as a hypothalamic neuropeptide to mediate metabolism and reproduction, food intake, and body weight. Alarin, a differentially spliced variant of GALP, is specifically involved in vasoactive effect in the skin and ganglionic differentiation in neuroblastic tumours. Dysregulation of galanin, GALP and alarin has been implicated in various neuroendocrine conditions such as nociception, Alzheimer’s disease, seizures, eating disorders, alcoholism, diabetes, and spinal cord conditions. Further delineation of the common and distinctive effects and mechanisms of various types of galanin family proteins could facilitate the design of therapeutic approaches for neuroendocrine diseases and spinal cord injury.